Analysis of congress destinations' competitiveness using importance performance competitor analysis. Issue 2 (3rd April 2017) - Caber, Meltem; Albayrak, Tahir; İsmayıllı, Türkan
ABSTRACT: To be competitive and successful in congress tourism, destinations must learn which congress tourism-related attributes are important and how they perform against their main competitors. This study identifies the importance and performance of destination attributes in Antalya, Turkey, and compares the position of these attributes to those of its main rival in congress tourism, İstanbul. Importance performance competitor analysis results show that, according to domestic participants, Antalya has to focus on "sight-seeing and cultural attractions" and "outside entertainment." For international participants, "climate, " "choice of meeting and housing properties, " and "suitability of conference facilities" exhibit higher performance in Antalya than İstanbul.